Fateless Never Faithless, Hope Less prey More, Bird and Beast, Soul Searching and Liminal - Nazzari, Anna (Venn Gallery, 2012)
5 pyrography images on rock maple by Anna Nazzari as part of the exhibition 'A magnificient world' held at the Venn Gallery, Perth, from 10 Feb - 16 Mar 2012. A Magnificent World brings together four Western Australian artists, Pia Bennett, Thea Costantino, Joshua Fitzpatrick and Anna Nazzari, to explore tales of sorcery, medieval miracles and the grotesque. Through varied media, each artist revisits these imaginings to uncover an evocative and fertile history of the absurd, fantastic and sublime.